Gay Hawkins, The Ethics of Waste: How We Relate to Rubbish - Macfarlane, Georgina (Journal for the study of religion, nature and culture, 2006)
Gay Hawkins, The Ethics of Waste: How We Relate to Rubbish (Oxford: Rowman & Littlefield, 2006), pp. xii + 151. Paperback $24.00, ISBN 0-7425-3013-2.